Peningkatan Aktivitas Belajar Menggunakan Model Pembelajaran Kooperatif STAD Pada Siswa Kelas III UPT SD Negeri 022 Dua Sepakat - Andri, Andri (Science and Education Journal (SICEDU), 2024)
This research discusses increasing learning activities using the STAD Cooperative Learning Model for Class III Students at UPT SD Negeri 022 Dua Sepakat. The aim of this research is to determine the increase in student learning activities in class III Thematic Learning at UPT SD Negeri 022 Dua Sepakat by implementing the STAD (Student Teams Achievement Division) model. This research is Classroom Action Research. The subjects of this research were class III students at UPT SD Negeri 022 Dua Sepakat while the object of the research was the Application of the STAD (Student Teams Achievement Division) Learning Model. To increase student learning activities in thematic learning. Data was obtained through observation, interviews and documentation. Data analysis was carried out using qualitative analysis consisting of data reduction, data presentation, drawing conclusions or verification. The research results show that the application of the STAD (Student Teams Achievement Division) learning model can increase student learning activities in the learning process. The increase in student learning activities can be measured from the evaluation of cycle I and cycle II. Student activity in cycle I was 56% in the 'quite active' category and student activity in cycle II was 92% in the 'very active' category. Thus, the research results at UPT SD Negeri 022 Dua Sepakat have been achieved well.